Circadian variation in acute myocardial infarct size assessed by cardiovascular magnetic resonance in reperfused STEMI patients. (1st March 2017) - Bulluck, Heerajnarain; Nicholas, Jennifer; Crimi, Gabriele; White, Steven K; Ludman, Andrew J; Pica, Silvia; Raineri, Claudia; Cabrera-Fuentes, Hector A; Yellon, Derek; Rodriguez-Palomares, Jose; Garcia-Dorado, David; Hausenloy, Derek J
Abstract: Objective: Clinical studies using serum cardiac biomarkers to investigate a circadian variation in acute myocardial infarct (MI) size in ST-segment elevation myocardial infarction (STEMI) patients reperfused by primary percutaneous coronary intervention (PPCI) have produced mixed results. We aimed to investigate this phenomenon using acute MI size measured by cardiovascular magnetic resonance (CMR). Methods: Patient-level data was obtained from 4 randomized controlled trials investigating the MI-limiting effects of cardioprotective therapies in this pooled analysis. The primary analysis was performed in those patients with no pre-infarct angina; duration of ischemia > 60 min and < 360 min; Thrombolysis In Myocardial Infarction (TIMI) flow pre-PPCI ≤ 1; TIMI flow post-PPCI 3; and no collateral flow. Results: 169 out of 376 patients with CMR data met the inclusion criteria for the primary analysis. A 24-hour circadian variation in acute MI size as a % of the area-at-risk (%AAR), after adjusting for confounders, was observed with a peak and nadir MI size in patients with symptom onset between 00:00 and 01:00 and between 12:00 and 13:00 respectively (difference from the average MI size 5.2%, 95%CI 1.1–9.4%; p  = 0.013). This was associated with a non-significant circadian variation in left ventricular ejection fraction (LVEF) (difference from the average LVEF 5.9%, 95%CI − 0.6–2.2%, p  = 0.073). There was no circadian variation in MI size or LVEF in the whole cohort. Conclusions: We report a circadian variation in acute MI size assessed by CMR in a subset of STEMI patients treated by PPCI, with the largest and smallest MI size occurring in patients with symptom onset between 00:00 and 01:00 and between 12:00 and 13:00 respectively.